Tolerance to winemaking stress conditions of Patagonian strains of Saccharomyces eubayanus and Saccharomyces uvarum - Origone, Andrea Cecilia (2017)
Aims: Evaluating the winemaking stress tolerance of a set of both Saccharomyces eubayanus and Saccharomyces uvarum strains from diverse Patagonian habitats. Methods and Results: Yeast strains growth was analysed under increasing ethanol concentrations; all of them were able to grow until 8% v/v ethanol. The effect of different temperature and pH conditions as well as at SO2 and hexose concentrations was evaluated by means of a central composite experimental design. Only two S. uvarum strains (NPCC 1289 and 1321) were able to grow in most stress conditions. Kinetic parameters analysed (μmax and λ) were statistically affected by temperature, pH and SO2, but not influenced by sugar concentration. The obtained growth model was used for predicting optimal growth conditions for both strains: 20°C, 0% w/v SO2 and pH 4·5. Conclusions: Strains from human-associated environments (chichas) presented the highest diversity in the response to different stress factors. Two S. uvarum strains from chichas demonstrated to be the most tolerant to winemaking conditions. Significance and Impact of the Study: This work evidenced the potential use of two S. uvarum yeast strains as starter cultures in wines fermented at low temperatures. Saccharomyces eubayanus was significantly affected by winemaking stress conditions, limiting its use in this industry.